Green Spaces in Bengaluru: Quantification through Geospatial Techniques - Ramachandra, T. V.; Aithal, Bharath H.; Kulkarni, Gouri; Vinay, S. (Indian Forester, 2017)
Green spaces in the urban landscape include public and private lands (parks, streets, backyards) consisting of trees, shrubs and, herbs, etc. COP21- recently concluded United Nations Climate conference at Paris acknowledges the need to limit warming towell below 2°C (3.6°F) above pre-industrial levels and the need to try to limit the temperature increase to 1.5°C through carbon neutrality and de-carbonisation mechanisms to avoid the worst climate impacts. World Health Organization stipulates minimum green space of 9.5 m2/person considering the services (oxygen, moderation of micro climate) and goods in the urban environment. Estimates indicate that about 6 kg of carbon is sequestered by a tree annually. Per capita respiratory carbon ranges from 192 to 328 kg/year depending on physiology of humans (525-900 gms/day/person depending on the age and physiology). Land use analysis show that the spatial extent of tree vegetation in Bangalore is 100.02 km2.(14.08%) and total number of trees in Bangalore is about 14,78,412 trees. Computation of trees per person show that Bangalore has one tree for every 7 persons, which highlights of crossing the threshold of urbanization. Overall improvements in human well-being in urban areas necessitate at least 33% green space that ensures at least 1.15 trees/person.